Development Of Novel And Environmentally Friendly Bio- Active Dermal Drug Delivery Wound Patch For Wound Healing - Sunder, Sharminy Pirem (2024)
Having a wound-healing dermal patch or medicated dressings that work well in wound healing and doesn't harm the environment is crucial. The commercially available synthetic dermal patches, plasters, and wound dressings in the market today are non- biodegradable, posing significant environmental issues. As a result, it is a great idea to reuse agro-waste to make a biodegradable dermal wound patch and, eventually, reduce environmental problems. Elaeis guineensis plant was reported with good wound healing activity in the literature and is commonly left as agro-waste at plantation areas. Therefore, this study was conducted to develop an environmentally friendly bio-active dermal drug-delivery wound patch containing E. guineensis for wound healing. The E. guineensis leaf was extracted using methanol by maceration extraction techniques, which yielded a dark brown paste-like crude extract. Subsequently, E. guineensis leaf extract was blended with polyvinyl alcohol (PVA) to develop a biodegradable dermal wound patch. Several physicochemical properties were evaluated and reported, such as appearance, average weight, thickness, moisture content, viscosity, and pH. The developed dermal wound patch had an average thickness of 0.020 mm and a weight of 3.87 mg with 17.61% of moisture content. The pH of the prepared dermal wound patch solution was 6.97, with a viscosity value of 2.56 cp. These results showed that the developed dermal wound patch is an appropriate and safe candidate to be utilized as a wound-healing agent.